2017
DOI: 10.1002/ajmg.b.32600
|View full text |Cite
|
Sign up to set email alerts
|

Nhe5 deficiency enhances learning and memory via upregulating Bdnf/TrkB signaling in mice

Abstract: Nhe5, a Na /H exchanger, is predominantly expressed in brain tissue and is proposed to act as a negative regulator of dendritic spine growth. Up to now, its physiological function in vivo remains unclear. Here we show that Nhe5-deficient mice exhibit markedly enhanced learning and memory in Morris water maze, novel object recognition, and passive avoidance task. Meanwhile, the pre- and post-synaptic components, synaptophysin (Syn) and post-synaptic density 95 (PSD95) expression levels were found increased in h… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
15
0

Year Published

2018
2018
2021
2021

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 27 publications
(15 citation statements)
references
References 38 publications
0
15
0
Order By: Relevance
“…However, the role of NO in each step of learning appears controversial and it might be task-dependent. ERK cascade is positively implicated in the development of fear conditioning, conditioned taste aversion memory, spatial memory, step-down inhibitory avoidance and object recognition memory ( Giovannini, 2006 ; Chen et al, 2017 ; Vithayathil et al, 2017 ). In our study, this pathway resulted to be activated upon cell exposure to GUA.…”
Section: Discussionmentioning
confidence: 99%
“…However, the role of NO in each step of learning appears controversial and it might be task-dependent. ERK cascade is positively implicated in the development of fear conditioning, conditioned taste aversion memory, spatial memory, step-down inhibitory avoidance and object recognition memory ( Giovannini, 2006 ; Chen et al, 2017 ; Vithayathil et al, 2017 ). In our study, this pathway resulted to be activated upon cell exposure to GUA.…”
Section: Discussionmentioning
confidence: 99%
“…TrkB-PLC/IP3 pathway on the inflammatory development of colitis. However, because the upstream BDNF of TrkB-PLC/IP3 pathway can improve the content of TNF-α and other inflammatory factor in depression, we speculated that the TrkB-PLC/IP3 pathway, as the downstream effector of BDNF, could also inhibit the inflammatory development in colitis [25][26][27][28].…”
Section: Discussionmentioning
confidence: 99%
“…Consistent with this hypothesis, BDNF and TrkB were widely located in the axon terminals (presynaptic sites) and dendrites (postsynaptic sites) of hippocampal neurons. The distribution and expression of synaptic proteins, such as SYN and PSD95, may be modulated by BDNF/TrkB signaling ( Jovanovic et al, 2000 ; Chen et al, 2017 ). It is well known that pCREB regulates the transcription of downstream genes including BDNF ( Reichardt, 2006 ; Lopez de Armentia et al, 2007 ).…”
Section: Discussionmentioning
confidence: 99%
“…Several studies have shown that BDNF/TrkB signaling is attenuated in the early stages of AD. Thus, the expression of SYN and PSD95 in the hippocampus may be increased by enhanced BDNF/TrkB signaling ( Chen et al, 2017 ).…”
Section: Introductionmentioning
confidence: 99%